2013
DOI: 10.1155/2013/213273
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Gastrointestinal Tuberculosis in Renal Transplant Patients

Abstract: Tuberculosis is a disease relatively frequent in renal transplant patients, presenting a wide variety of clinical manifestations, often involving various organs and potentially fatal. Gastrointestinal tuberculosis, although rare in the general population, is about 50 times more frequent in renal transplant patients. Intestinal tuberculosis has a very difficult investigational approach, requiring a high clinical suspicion for its diagnosis. Therapeutic options may be a problem in the context of an immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…Rifampicin is a strong inducer of microsomal enzyme P450 3A4, which leads to increased metabolism of calcineurin-inhibitors, rapamycin and steroids [ 24 ]. Rifampicin reduces plasma levels of cyclosporine 2-5 fold and tacrolimus 4-10 fold [ 1 ], which increases the risk of rejection [ 13 ]. Moreover, common TB medications may lead to interactions with other required drugs, as documented with our case.…”
Section: Discussionmentioning
confidence: 99%
“…Lungs are commonly involved. In renal transplant (RT) recipients, extrapulmonary (occurring in 15%) and disseminated diseases (33-49%) are very frequent [1], while intestinal involvement is extremely rare, with a reported prevalence between 0.2% and 0.6% [2]. Atypical presentation is the rule in immunocompromised patients, while high clinical suspicion is required.…”
mentioning
confidence: 99%
“…Gastrointestinal manifestation is infrequent, but potentially lethal. It appears frequently during the early PT period [1]. Commonly, it is presented with atypical and vague symptoms such as abdominal pain, fever, weight loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation